2022
DOI: 10.1186/s12915-022-01328-w
|View full text |Cite
|
Sign up to set email alerts
|

Inherent constraints on a polyfunctional tissue lead to a reproduction-immunity tradeoff

Abstract: Background Single tissues can have multiple functions, which can result in constraints, impaired function, and tradeoffs. The insect fat body performs remarkably diverse functions including metabolic control, reproductive provisioning, and systemic immune responses. How polyfunctional tissues simultaneously execute multiple distinct physiological functions is generally unknown. Immunity and reproduction are observed to trade off in many organisms but the mechanistic basis for this tradeoff is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Nutritional stress has been shown to upregulate immune function and is dependent on insulin signalling (Agrawal et al, 2016). Since fat body is the major immune as well as metabolic tissue of Drosophila (Gupta et al, 2022) it is likely that the results obtained in this study indicate immune‐metabolic trade‐offs. FEJ and FLJ populations are under selection for faster pre‐adult development with their egg to adult development time being 6.5 and 7.5 days respectively, due to which the larval duration especially the post‐critical duration is drastically reduced and thus they might be under nutritional deprivation which induces inflammation even under uninfected state.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Nutritional stress has been shown to upregulate immune function and is dependent on insulin signalling (Agrawal et al, 2016). Since fat body is the major immune as well as metabolic tissue of Drosophila (Gupta et al, 2022) it is likely that the results obtained in this study indicate immune‐metabolic trade‐offs. FEJ and FLJ populations are under selection for faster pre‐adult development with their egg to adult development time being 6.5 and 7.5 days respectively, due to which the larval duration especially the post‐critical duration is drastically reduced and thus they might be under nutritional deprivation which induces inflammation even under uninfected state.…”
Section: Discussionmentioning
confidence: 76%
“…Nutritional stress has been shown to upregulate immune function and is dependent on insulin signalling (Agrawal et al, 2016). Since fat body is the major immune as well as metabolic tissue of Drosophila (Gupta et al, 2022) Suzawa et al, 2019). We measured the transcript levels of 4eBP/ Thor as the read out of insulin signaling (Teleman et al, 2005) and found that there was significant increase in Thor level in both, FEJs and FLJs compared to JBs (Figure 6b) indicating reduced insulin signalling in them.…”
Section: Discussionmentioning
confidence: 95%
“…This is probably owing to the high metabolic cost imposed by higher haemocyte numbers, reducing available fat body lipid stores [52]. Another example is the trade-off between reproduction and immunity, as both sides impose a high metabolic demand on the insect fat body in females [53][54][55]. While there is renewed attention on how positive selection promotes AMP polymorphisms, we know less about the evolutionary forces that maintains these alternate alleles [41,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several essential amino acids (methionine, valine, isoleucine and in particular leucine, all less abundant in Selected flies) act as signaling molecules that promote protein synthesis by activating TOR complex 1 (Wolfson, et al 2016; Antikainen, et al 2017; Gu, et al 2022). Most of protein synthesis activity in adult female fat bodies is directed towards synthesizing egg proteins (Piper, et al 2017; Gupta, et al 2022). Thus, while we have not demonstrated a direct causal link, lower abundance of most essential amino acids in the Selected flies is consistent with their lower fecundity.…”
Section: Discussionmentioning
confidence: 99%